2018
DOI: 10.1089/scd.2018.0042
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Engraftment Promotes Differentiation of Alveolar Epithelial Cells from Human Embryonic Stem Cell Derived Lung Organoids

Abstract: Human embryonic stem cell (hESC) derived 3D human lung organoids (HLOs) provide a promising model to study human lung development and disease. HLOs containing proximal or/and immature distal airway epithelial cells have been successfully generated in vitro, such as early staged alveolar type 2 (AT2) cells (SPC/SOX9) and immature alveolar type 1 (AT1) cells (HOPX/SOX9). When HLOs were transplanted into immunocompromised mice for further differentiation in vivo, only few distal epithelial cells could be observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…During mouse lung development, AT1 and AT2 cells are generated directly from a bipotent progenitor [10,11]. It remains to be determined whether or not a similar bipotent progenitor population exists in the human fetal lung; however, cells expressing both an AT2 cell marker (surfactant protein C (Sftpc)) and an AT1 cell marker (podoplanin) were observed in long-term cultured organoids derived from human embryonic stem cells [12]. In adults, AT2 cells were shown to give rise to AT1 cells;…”
Section: Stem/progenitor Cells That Generatementioning
confidence: 99%
“…During mouse lung development, AT1 and AT2 cells are generated directly from a bipotent progenitor [10,11]. It remains to be determined whether or not a similar bipotent progenitor population exists in the human fetal lung; however, cells expressing both an AT2 cell marker (surfactant protein C (Sftpc)) and an AT1 cell marker (podoplanin) were observed in long-term cultured organoids derived from human embryonic stem cells [12]. In adults, AT2 cells were shown to give rise to AT1 cells;…”
Section: Stem/progenitor Cells That Generatementioning
confidence: 99%
“…Limited access to primary human ATII cells, particularly from diseased patients, and the rapid loss of ATII marker expression and function when cultured in vitro, make it challenging to study the role of human ATII cells in IPF 19 . Recent advances have led to the successful derivation of ATII‐like cells from human pluripotent stem cells (hPSCs, including both embryonic stem cells and induced pluripotent stem cells (iPSCs)), providing a promising alternative cell source for in vitro disease modeling 20‐26 . Previous reports on hPSC‐derived lung cells showed that despite their phenotypic similarities to mature lung epithelium, these models are equivalent to human fetal lung cells, rather than representing an adult state 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Limited access to primary human ATII cells, particularly from diseased patients, and the rapid loss of ATII marker expression and function when cultured in vitro, make it challenging to study the role of human ATII cells in IPF (19). Recent advances have led to the successful derivation of ATII-like cells from human pluripotent stem cells (hPSCs, including both embryonic stem cells and induced pluripotent stem cells), providing a promising alternative cell source for in vitro disease modeling (20)(21)(22)(23)(24)(25)(26). Previous reports on hPSC-derived lung cells showed that despite their phenotypic similarities to mature lung epithelium, these models are equivalent to human fetal lung cells, rather than representing an adult state (27,28).…”
Section: Introductionmentioning
confidence: 99%